TSUNAMI RISK ASSESSMENT IN PACITAN, EAST JAVA USING HYPOTHETIC TSUNAMI SIMULATION - Tilangsari, Novita
The historical record does not show significant earthquakes generated tsunamis in the southern waters of Java, but Banyuwangi Tsunami, 1994 and Pangandaran Tsunami, 2006. Those magnitude moment’s are 7,8 (1994) and 7,7 (2006). Both tsunamis hit Banyuwangi resulted 14 meter high on the land and 21 meter extreme run-up in West Java that generates a seismic gap that might be a source of tsunami in the future and also many studies had suggested those tsunami above are type of tsunami earthquake. Pacitan Bay is located on the southern coast of Java Island faces Indian Ocean directly and is in the seismic gap. Simulations were done using COMCOT v.1.7 software with Global Mapper 15, Matlab, and ArcGIS 10.2.2 as supporting software and also InaSAFE plugin to calculate tsunami risk in Pacitan District. There are three tsunami scenarios, for magnitude Mw=7,7, 8,3, and 8,8. The simulation results height, arrival time, and run-up of tsunamis are used as hazard parameter, while population, road, and buildings are as vulnerability parameter. The tsunami arrive after 38,53, 38,27, dan 39,25 minutes with a tsunami height about 1,92 meters, 3,83 meters, and 9,75 meters for Mw=7,7, Mw=8,3, and Mw=8,8, and flowdepth is about 0 – 1,7 meters. Sidoharjo is the most heavily affected villages. The three tsunami simulations flooded the same areas but resulting the different flowdepth, it caused by Pacitan District that face directly to the clift.